Bacterial Etiology and Antibiotic Susceptibility in Isolates from Conjunctivitis Patients in Tripoli, Libya - Najla Elyounsi; Soomia Al-Haddad; Asma Abolqasim; Abdurraouf Said; Hosam Elmahmoudi (AlQalam Journal of Medical and Applied Sciences, 2024)
Acute conjunctivitis is described as inflammation of the conjunctiva that lasts less than 3 to 4 weeks, showing cellular infiltration and exudation. Conjunctivitis can cause significant and lasting harm to the eye, resulting in severe inflammation in the corneal lid. This study seeks to isolate and identify the particular bacterial pathogens responsible for conjunctivitis in patients at Tripoli Eye Hospital. Collection of bacterial samples from patients with conjunctivitis was conducted at the ophthalmic consultative clinic within Tripoli Eye Hospital, Libya between September 2021 and January 2022. Tests were done to separate bacterial pathogens causing conjunctivitis and to test their resistance to antibiotics. Among 140 samples, bacterial infection was detected in 86% of cases while 14% yielded negative results. Males had a higher prevalence of bacterial infections at 63% in comparison to females. Both male and female individuals aged 60-79 years had the highest percentage of bacterial conjunctivitis cases at 51%. Segregation tests showed that the majority (82%) were Gram-positive, while a minority (18%) were Gram-negative, with Staphylococcus aureus being the most prevalent bacteria (35%), closely followed by Staphylococcus epidermidis (32%). Streptococcal pneumoniae and Enterobacter spp had rates of 2% which were lower. The majority of organisms showed sensitivity to levofloxacin (43%), while there was only a small amount of resistance to polymyxin B (4%). Professional attention and microbiological research are crucial for verifying clinical diagnoses and carrying out suitable and efficient treatments. التهاب الملتحمة الحاد يُعرف بأنه التهاب الملتحمة الذي يستمر من 3 إلى 4 أسابيع، مع ظهور إفرازات قيحية أو مخاطية. قد يسبب التهاب الملتحمة أضرارًا خطيرة ودائمة للعين، مما يؤدي إلى التهاب شديد في غشاء القرنية. تهدف هذه الدراسة إلى عزل وتحديد المسببات البكتيرية لالتهاب الملتحمة لدى المرضى الذين يترددون على مستشفى طرابلس للعيون، ليبيا. جمعت العينات المعزولة من مرضى التهاب الملتحمة في العيادات الاستشارية لطب العيون داخل المستشفى خلال الفترة ما بين سبتمبر2021 ويناير 2022. ثم إجراء اختبارات العزل لتشخيص المسببات البكتيرية لالتهاب الملتحمة، وكذلك اختبار حساسية السلالات البكتيرية للمضادات الحيوية. من بين 140 عينة، تم الكشف عن العدوى البكتيرية في 86٪ من الحالات بينما أسفرت 14٪ من الحالات عن نتائج سلبية. وكانت نسبة انتشار التهاب الملتحمة البكتيري أعلى عند الرجال منها عند النساء بنسبة (63%). في حين كان لدى كل من الذكور والإناث في الفئة العمرية (60-79) أعلى نسبة انتشار لالتهاب الملتحمة الجرثومي بنسبة 51٪. أظهر اختبار العزل أن (82%) من العينات المعزولة كانت (موجبة الجرام)، مقابل (18%) منها كانت (سلبية جرام)، حيث كانت المكورات العنقودية الذهبية هي الأكثر شيوعا بنسبة (35%) تليها المكورات العنقودية الجلدية بنسبة (32%)، بينما كانت أقل المعدلات هي المكورات العقدية الرئوية والأمعائية بنسبة (2%). أظهرت معظم العزلات البكترية حساسية لليفوفلوكساسين بنسبة (43٪)، في المقابل كانت محدودة الحساسية للمضاد الحيوي بوليميكسين (4٪). تعد الدراسات الميكروبيولوجية ضرورية لتحقيق اختيار العلاج المناسب والفعال